The use of mechanotherapy means in basketball players recovery after the injuries of the lower extremities - Zheleznyj, O. D.; Zasik G. B.; Mukhin, V. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim is to develop methods of physical rehabilitation of basketball players with injuries of the lower extremities. Summarizes the experience of use of mechanical therapy for the recovery of athletes with injuries to the lower extremities. Analyzed the nature of lower extremity injuries and their consequences. The methods of application of mechanical therapy using a simulator developed universal and local fatty clay as a means of physical therapy. It is proved that the method developed by the authors provided a mechanotherapy achieve the required level of mobility in the joints and improve range of body functions. Found that in the process of applying the developed program of rehabilitation basketball players with injuries of the lower extremities most effective in complex physical rehabilitation was value: therapeutic physical training with mechanotherapy + physical therapy with curative mud + therapeutic massage. Technique introduced to the work of medical and health-improving establishments and educational institutions of Ukraine Ministry of Education and Science of Ukraine.